2016
DOI: 10.31768/2312-8852.2016.38(3):146-157
|View full text |Cite
|
Sign up to set email alerts
|

The use of proTeomic Technologies in breasT cancer research

Abstract: The main findings in the field of breast cancer proteomic research as well as modern strategies, technologies and methods of validation are reviewed. A special attention is focused on validated proteomic biomarkers of breast cancer. The data on proteomic profiling of stroma, tumor microenvironment, involvement of proteins in tumor progression, invasion and metastasis, and mechanisms of action of new generation drugs, are analyzed. The results of proteomic analysis are of high clinical importance and significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Different proteomic technologies have identified unique proteome patterns that can diagnose BC in different clinical stages and recognize different outcome and response to therapy (Mazur and Pyatchanina, 2016). Furthermore, reproducibility of MS based protein profiles for diagnosis of BC across clinical studies has been demonstrated in systematic review (Callesen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different proteomic technologies have identified unique proteome patterns that can diagnose BC in different clinical stages and recognize different outcome and response to therapy (Mazur and Pyatchanina, 2016). Furthermore, reproducibility of MS based protein profiles for diagnosis of BC across clinical studies has been demonstrated in systematic review (Callesen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometry outperformed other techniques in its ability to detect hundreds of proteins in a sole experiment. These proteins are either up or down regulated when comparing the proteomic profiling between malignant and non malignant biological fluids (Mazur and Pyatchanina, 2016;Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics allows monitoring of the changes in the relative amount and the distribution of proteins that are encoded by cancer genes in tumor tissues or compares the expression of proteins in tumors and corresponding normal tissue. Thus modern proteomic technologies, utilizing gel electrophoresis (1D- or 2D-PAGE and 2D-DIGE) and liquid chromatography (LC) combined with MS, have recently been increasingly applied to the study of carcinoma. The use of LC–MS/MS together with quantitative methods, such as, isotope-coded affinity tagging (ICAT–LC–MS/MS), isobaric tagging for relative and absolute quantitation (iTRAQ–LC–MS/MS), or stable isotope labeling with amino acids in cell cultures (SILAC–LC–MS/MS), is promising for the discovery of new cancer protein biomarkers …”
Section: Cancer Glycoproteomicsmentioning
confidence: 99%
“…The steeply growing number of publications related to cancer proteomics and glycoproteomics proves that this is a hot topic (Figure ). A summary of proteomic approaches, advancements, and their applications for profiling analyses of tumor tissues/cell has been published in various reviews, but only a few of them are especially focused on breast cancer. ,,, …”
Section: Cancer Glycoproteomicsmentioning
confidence: 99%